Curvas de crescimento e deposição de nutrientes no corpo e nos ossos de frangas de duas linhagens comerciais alimentadas com diferentes níveis de fibra em detergente neutro na ração de crescimento (7 a 17 semanas de idade) - Sucupira, Francislene Silveira (2014)
The objective was to evaluate the effect of using different levels of neutral detergent fiber (NDF) in diets for hens of two commercial layer-hen strains from 7 to 17 weeks of age on the growth curve and deposition of body components and bones. A total of 648 birds from each strain were distributed in a completely randomized design in a 3 × 2 factorial arrangement consisting of three levels of NDF and two strains, with four replicates of 54 birds. The tested NDF levels were 14.5, 16.5 and 18.5%. Additionally, live weight, feather weight, body composition of protein, ash and water, bones weight, bones length and bones composition of protein, ash and water were evaluated. Growth curves were determined by applying the data on Gompertz function. According to the results, there was no interaction among factors, strain and NDF levels for the parameters of the equation of Gompertz determined for all evaluated traits. The NDF levels of the diet affected the estimates of weight at maturity and water deposition in the carcass. The level of 14.5% NDF allowed for greater weight at maturity (Wm), greater age at maximum growth (t*) and lower maturity rate (b) than the other tested levels. There was no influence of NDF levels tested on the parameters of the growth curve for weight and length of the tibia and femur (P <0.05). There was no influence of NDF levels tested on the estimates of the parameters of the Gompertz equation for the composition of water, protein and ash of the tibia and fêmur (P <0.05). The level of NDF in the ration of growing can be used to modify the growth curve of pullets, being able to control the body weight gain by increasing its level in the ration without changing the deposition of water, ash and protein in the carcass. Pullets fed diets containing up to 18.5% inclusion of NDF, during 7-17 weeks of age, showed no changes in the curves of growth and nutrient deposition in the tibia and femur.